2016
DOI: 10.1213/ane.0000000000001327
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Arm Positioning on Ultrasonic Visualization of the Subclavian Vein: An Anatomical Ultrasound Study in Healthy Volunteers

Abstract: We hypothesized that placing the arm in 90° abduction, through 90° flexion and 90° external rotation, could improve ultrasound visualization of the subclavian vein. In 49 healthy volunteers, a single operator performed a view of the subclavian vein in neutral position and abduction position. A second blinded operator measured the cross-sectional area of the subclavian vein. Abduction position increased the cross-sectional area of the subclavian vein from 124 ± 46 (mean ± SD) to 162 ± 58 mm (P = 0.001). An incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 15 publications
1
22
1
1
Order By: Relevance
“…Because the cross-sectional area of the vein is an important determinant of successful central venous catheterization, various maneuvers to increase the csSCV have been introduced. Among them, 30°head rotation to the ipsilateral side of the operator and arm positioning with 90°abduction, 90°flexion, and 90°external rotation have been shown to increase the csSCV [16,18]. However, head rotation can disturb cerebral venous drainage, which may increase the intracranial pressure (ICP) [21], and specific arm positioning requires an additional device to maintain arm placement [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the cross-sectional area of the vein is an important determinant of successful central venous catheterization, various maneuvers to increase the csSCV have been introduced. Among them, 30°head rotation to the ipsilateral side of the operator and arm positioning with 90°abduction, 90°flexion, and 90°external rotation have been shown to increase the csSCV [16,18]. However, head rotation can disturb cerebral venous drainage, which may increase the intracranial pressure (ICP) [21], and specific arm positioning requires an additional device to maintain arm placement [18].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 30° head rotation to the ipsilateral side of the operator and arm positioning with 90° abduction, 90° flexion, and 90° external rotation have been shown to increase the csSCV [ 16 , 18 ]. However, head rotation can disturb cerebral venous drainage, which may increase the intracranial pressure (ICP) [ 21 ], and specific arm positioning requires an additional device to maintain arm placement [ 18 ]. The Trendelenburg position increases the csSCV compared with the supine position [ 22 ], but it may increase the ICP, especially in patients with intracranial space-occupying lesions [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 While inserting CVCs faulty technique can result in damage to blood vessels, trauma to adjacent nerves or development of pneumothorax and hemothorax. 4,5 Patients with indwelling CVCs are at enhanced risk of developing various catheter related infections (CRI) such as localized insertion site infections, septic thrombophlebitis, catheter related blood stream infections (CRBSI), bacteremia, metastatic infections, sepsis and if not promptly treated can result in patient's death. 6,7 Colonization of CVC tips and resultant healthcare associated bacteremia and septicemia can contribute towards enhanced patient morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Smaller studies have shown that patient positioning during cannulation of the subclavian vein (e.g., turning the head to the contralateral side, shoulder-pulled-downward position, and abducted position of arm) can alter the relationship between the subclavian vein and the internal jugular vein and can also alter the cross-sectional area of the vein, thus potentially affecting the safety and success of cannulation [ 4 , 5 ]. Further well designed studies should try to explore the influence of these various patient positions on ultrasound-guided subclavian venous cannulation.…”
mentioning
confidence: 99%